Penguatan Karakter Islami Anak melalui Model Qur’anic Project-Based Learning (Q-PjBL) di Rumah Edukasi Qur’ani (REQ) - Gunawan, Sardi; Agustina, Yulius; Shafwan, Muhammad Hambal (Philosophiamundi, 2025)
This community engagement program aims to strengthen children’s Islamic character through the implementation of the Qur’anic Project-Based Learning (Q-PjBL) model at Rumah Edukasi Qur’ani (REQ). The initiative was developed in response to the need for character education that integrates cognitive, affective, and psychomotor aspects in a practical and meaningful way. The method consisted of four stages: needs analysis, Qur’anic project design, project-based implementation, and character evaluation through behavioral observation, daily reflection, and parental feedback. The results indicate a significant improvement in children’s understanding of Qur’anic verses and their moral values, including discipline, responsibility, honesty, cooperation, and proper manners. The Q-PjBL model proved effective in creating an active, contextual, and meaningful learning environment that fosters intrinsic motivation to apply Qur’anic values in daily life. In conclusion, Q-PjBL is a relevant and sustainable approach for character development in non-formal Islamic education institutions and has strong potential for replication in similar educational settings